Demographically Corrected Normative Standards for the Spanish Language Version of the NIH Toolbox Cognition Battery. (28th January 2016) - Casaletto, Kaitlin B.; Umlauf, Anya; Marquine, Maria; Beaumont, Jennifer L.; Mungas, Daniel; Gershon, Richard; Slotkin, Jerry; Akshoomoff, Natacha; Heaton, Robert K.
Abstract: Hispanics are the fastest growing ethnicity in the United States, yet there are limited well-validated neuropsychological tools in Spanish, and an even greater paucity of normative standards representing this population. The Spanish NIH Toolbox Cognition Battery (NIHTB-CB) is a novel neurocognitive screener; however, the original norms were developed combining Spanish- and English-versions of the battery. We developed normative standards for the Spanish NIHTB-CB, fully adjusting for demographic variables and based entirely on a Spanish-speaking sample. A total of 408 Spanish-speaking neurologically healthy adults (ages 18–85 years) and 496 children (ages 3–7 years) completed the NIH Toolbox norming project. We developed three types of scores: uncorrected based on the entire Spanish-speaking cohort, age-corrected, and fully demographically corrected (age, education, sex) scores for each of the seven NIHTB-CB tests and three composites (Fluid, Crystallized, Total Composites). Corrected scores were developed using polynomial regression models. Demographic factors demonstrated medium-to-large effects on uncorrected NIHTB-CB scores in a pattern that differed from that observed on the English NIHTB-CB. For example, in Spanish-speaking adults, education was more strongly associated with Fluid scores, but showed the strongest association with Crystallized scores among English-speaking adults. Demographic factors were no longer associated with fully corrected scores. The original norms were not successful in eliminating demographic effects, overestimating children's performances, and underestimating adults' performances on the Spanish NIHTB-CB. The disparate pattern of demographic associations on the Spanish versus English NIHTB-CB supports the need for distinct normative standards developed separately for each population. Fully adjusted scores presented here will aid in more accurately characterizing acquired brain dysfunction among U.S. Spanish-speakers. ( JINS, 2016, 21, 364–374)